Методика розрахунку параметрів пристрою на основі інжектора вентурі для фертигації плодових насаджень - Сушко, Сергій Леонідович; Чижиков, Іван Олександрович; Sushko, Serhii; Chyzhykov, Ivan (Запоріжжя : 2023, 2023)
UA: Одним з найбільш розповсюдженим у застосуванні пристроєм для внесення добрив з поливною водою (фертигації) є інжектор Вентурі. Для розрахунку струминного апарату (насоса, ежектора, інжектора) необхідно визначити такі гідравлічні та геометричні параметри: 1) витрати робочої та всмоктуваної рідини; 2) питомі енергії (повні тиски) робочої, всмоктуваної та змішаної рідин; 3) площі зрізу робочого сопла або його діаметр, площу поперечного перерізу камери змішування або його діаметр. В статті наведено результати розробки спрощеної методики розрахунку пристрою фертигації, що використовує інжектор Вентурі в якості насосу для подачі маточного розчина добрив у поливну воду при зрошенні плодових насаджень. Побудовано характеристики інжектора у відносній формі для випадку, коли площа входу в камеру зміщення інжектора перевищує у два рази площу робочого сопла. Встановлено, що в такій конфігурації максимальне значення ККД інжектора досягається при відносній витраті q=0,6. При цьому відносний напір складатиме h=0,37, а коефіцієнт витрат робочого сопла р.с= 0,21. Наведено результати розрахунків витрати води через інжектор та об’єму інжекції залежно від геометричних параметрів інжектора та зміни тиску води. EN: Fruit trees, growing for many years in one place and distinguished by high productivity, absorb a large amount of nutrients from the soil. Numerous experiments of scientific institutions and the practice of advanced farms have proven the high efficiency of the optimal fertilizer application system in gardens. Significant areas of modern orchards are equipped with drip irrigation systems, in which mineral fertilizers are applied locally with irrigation water (fertigation). Fertigation allows you to constantly maintain optimal soil moisture and supply plants with small doses of a balanced amount of nutrients during the growing season. One of the most used devices for applying fertilizers with irrigation water is the Venturi injector. This system is easy to maintain and relatively inexpensive, providing the supply of dissolved concentrated fertilizers with great precision into the irrigation pipeline. Currently, there is no general analytical theory that allows the calculation of jet devices (pumps, hydraulic elevators, ejectors, injectors) without using empirical formulas and quantities. Methods based on the following theories are proposed for the calculation of jet devices: theory of mixing of two flows; theories of the propagation of a jet in a mass of liquid that is at rest or moving; mechanics of bodies of variable mass. To calculate the jet device (pump, ejector, injector), it is necessary to determine the following hydraulic and geometric parameters: 1) consumption of working and suction fluid 2) specific energy (total pressure) of working, suction and mixed fluids; 3) cross-sectional area of the working nozzle or its diameter, cross-sectional area of the mixing chamber or its diameter. Thus, in order to calculate a jet pump, it is necessary to determine seven unknown quantities of liquids, that is, seven equations must be compiled. To solve the given problem, it is desirable to have a simplified method of calculation that gives results with sufficient accuracy for practical use. The article presents the results of the development of a simplified method of calculating the fertigation device, which uses a Venturi injector as a pump for feeding the mother solution of fertilizers into the irrigation water when irrigating fruit plantations. The characteristics of the injector are constructed in relative form for the case when the area of the entrance to the displacement chamber of the injector exceeds twice the area of the working nozzle. It was found that in such a configuration, the maximum value of the injector efficiency is reached at a relative flow q=0.6. At the same time, the relative pressure will be h=0.37, and the flow rate of the working nozzle р.с= 0.21The results of calculations of water flow through the injector and injection volume depending on the geometric parameters of the injector and changes in water pressure are given.
Method for calculating device parameters based on venturi injector for fruit plant fertigation
Keywords: мінеральні добрива; багаторічні насадження; поливна вода; насос; вузол фертигації; методика розрахунку; тиск; напір; mineral fertilizers; perennial plantings; irrigation water; pump; fertigation unit; calculation method; pressure; pressure